Finance and Development, September 2002. (Finance and Development; Finance and Development ;, 2002)
This paper focuses on the Doha Development Agenda. The paper highlights that over the past 20 years, world trade has grown twice as fast as world real GDP, deepening economic integration and raising living standards. The paper underscores that the launch of a new trade round in Doha in November 2001 was a major breakthrough following the debacle in Seattle in 1999. The new round places the needs and interests of developing countries at the heart of its work, but a successful outcome for rich and poor nations alike is by no means a foregone conclusion.